Previsão da estrutura temporal da taxa de juro na zona Euro : aproximação paramétrica e por métodos de aprendizagem automática - Garcia, Inês Regina Portela Costa (2016)
Dissertation presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Risk Analysis and Management